A review of the recognition-based graphical password - Islam, Amanul; Por, Lip Yee; Othman, Fazidah; Chin, Soon Ku (2017)
This paper reviews the recognition-based graphical password system. Twenty-five recognition-based graphical password systems are studied and analyzed with regards to their security threats. Countermeasures and suggestions are given to prevent and reduce the security threats. A comparison summary of the selected recognition-based graphical password system is deliberated at the end of this paper.